The Relevance of African Indigenous Proverbs in the Development of Pupils’ Learning Competencies - Carine, Ayuk; Oyoma , Chongwain (American Journal of Education and Practice, 2023)
Purpose: This study investigated the impact of African indigenous proverbs in the development of pupils' learning competencies. The objective of this study is to provide an insight of how proverbs can be useful in the development of pupils' cognitive competencies and to find the impact that, the values of African indigenous proverbs have in the education of pupils in the Cameroon educational system. The descriptive survey research design was used for the study and the sampled population consisted of 300 pupils of three primary schools in Bamenda III municipality namely; Government Practicing School Bamenda, Group A, Government Practicing School, Nibung and Government Practicing School Bamenda, Group B in Bamenda III Municipality. The simple random sampling technique was used to obtain participants (pupils) to provide answers to the questionnaire items and the purposive and convenient sampling techniques were employed to get participants (parents) for the structured interviews. Microsoft Excel and the Statistical Package for the Social Sciences (SPSS) were used to analyze the data. Mean and standard deviation were used to analyse research questions while regression analysis was used to test hypotheses. Methodology: Descriptive statistics (tables, percentages and charts) as well as inferential statistics (Regression Analysis) were employed for data analysis. Findings: The findings of the study revealed that 32.3% of the variations accounted for by indigenous proverbs. Recommendations: From the above findings, it was recommended that indigenous proverbs should be included in school curriculum content especially in literal studies. And also, teachers should be encouraged to integrate and to make use of them in their teaching methods.